Drug related problems associated with the psychoactive drugs used on geriatric, hospitalized patients - Ortega López Irma Leonor; Verdecia Rosés Miguel Ernesto (Universidade de São Paulo, 2012)
A prospective study was carried out, to identify the drug related problems and to prevent or to solve the negative outcomes associated with medication of the geriatric patients that consumed psychoactive drugs, who were hospitalized. The study was carried out according to the DADER Method of Pharmacotherapy Monitoring, adapted to the Hospital's environment and the theoretical rationale of the Third Consent of Granada was assumed, for the considerations related to the drug related problems and the negative outcomes associated with medication. Thirty five patients were included whose ages ranged between the 60 and 90 years. Thirty six negative associated outcomes were identified, in 34 patients that represented 97.14% incidence. A prevalence of the negative outcomes associated with the necessity was observed, followed by those associated with the security. The inadequate drug uses was the drug related problem that prevailed in the sample. The psychoactive drugs that were related with these results were mainly the anxiolytics, meprobamate and the neuroleptics. Some 82.35% of the interventions were accepted, achieving resolution of 47.06% of the negative outcomes associated with medication. Foi realizada uma pesquisa de intervenção, prospectiva, a fim de identificar problemas relacionados aos medicamentos e evitar ou resolver resultados negativos daí decorrentes, em pacientes idosos que faziam uso de medicamentos psicotrópicos e que foram internados. O estudo foi realizado de acordo com o método DADER para o acompanhamento farmacoterapêutico e assumiram-se os pressupostos teóricos do III Consenso de Granada, as considerações relacionadas com os problemas dos fármacos e os resultados negativos associados à medicação. Foram incluídos 35 pacientes com idades entre 60 e 90 anos. Trinta e seis RM foram identificados em 34 pacientes representando incidência de 97,14% e a prevalência foi observada para os resultados negativos associados com a necessidade, seguidos por aqueles relacionados à segurança. O uso indevido de fármacos foi os problema mais frequente na amostra. Os psicofármacos mais implicados foram os ansiolíticos, meprobamato e neurolépticos. Das intervenções, 82,35% foram aceitas, alcançando 47,06% de resolução dos resultados negativos associados à medicação.